LOCAL WISDOM AS A STRATEGIC APPROACH FOR SUSTAINABLE FISHERIES RESOURCE MANAGEMENT: A CASE STUDY IN THE RIVERINE WATERS OF BANYUMAS REGENCY, CENTRAL JAVA - Putera, I Gede Suweda Anggana; Pramono, Taufik Budhi; Junaidi, Teuku; Salsabila, Sahda; Hutabarat, Philipus Uli Basa; Firdaus, Abdul Malik; Permatasari, Mahardhika Nur (Jurnal Perikanan Unram, 2025)
The riverine ecosystems traversing Banyumas Regency through the Serayu Watershed (DAS Serayu) serve as strategic freshwater resource zones, supporting both ecological functions and local livelihoods through economically valuable fish species. However, anthropogenic pressures such as domestic waste pollution, land-use conversion, overfishing, and the use of destructive fishing methods have led to significant ecological degradation. This study aims to: (1) identify key issues in the management of riverine fish resources in Banyumas as common property resources, and (2) explore community-based local wisdom practices implemented for sustainable fisheries conservation. Conducted in February 2025 at the Pokmaswas Lestari Kaliku post in Rawalo Subdistrict, this research employed a qualitative descriptive approach, utilizing field observations, in-depth interviews, and FGDs with 38 respondents drawn from key institutions, including the Provincial Marine and Fisheries Office, Banyumas Fisheries and Livestock Office, local fishery extension workers, the Rekam Jejak Nusantara NGO, and 9 active community monitoring groups (Pokmaswas). Findings reveal that Pokmaswas have adopted various forms of traditional ecological knowledge as management instruments, including: (1) prohibition of hazardous fishing gear (poison and electric shock), (2) establishment of core conservation zones (fish sanctuaries), (3) periodic restocking of indigenous fish species, (4) enforcement patrols against illegal and destructive fishing practices, and (5) public education and outreach initiatives on river ecosystem conservation. These practices demonstrate not only ecological effectiveness but also the critical role of community participation in achieving sustainable fisheries management. In conclusion, local wisdom-based approaches prove to be strategic and effective in addressing complex aquatic resource management challenges, offering an integrated pathway between conservation imperatives and the socio-economic needs of riverside communities.